Metabolic perturbation of epigenome by inhibiting -adenosylhomocysteine hydrolase elicits senescence through DNA damage response in hepatoma cells - Guozhen Wu; Ning Wang; Ying Luo; Yanyan Zhang; Peng Wang; Zhengyan Zhu; Yingtang Gao; Zhi Du; Bin Yang (Tumor Biology)
Cellular senescence is a key physiological barrier against tumor and represents an option for therapeutic intervention. One pivotal intracellular stimulus causing senescence is DNA damage response, while the senescence-associated heterochromatin in cancer limits the strength of the DNA damage response to endogenous genotoxic stress or DNA-damaging agents. Therefore, targeting the maintenance of compacted chromatin in cancer cells represents an optional intervention to improve the therapeutic efficacy in cancer treatment. Given a crosstalk between methionine cycle and histone methylation, we hypothesize that pharmacologically disrupting methylation potential, defined as the ratio of cellular S -adenosylmethionine to S -adenosylhomocysteine, could affect the chromatin structures in cancer cells and thus enhance their sensitivity to DNA damage response signaling. Our results showed that 3-deazaneplanocin A, a chemical inhibitor of S -adenosylhomocysteine hydrolase, elicited a typical cellular senescence in hepatoma cells. Therapy-induced senescence by 3-deazaneplanocin A was mediated through p53–p21 pathway and triggered by enhanced ataxia-telangiectasia mutated activation related to chromatin changes. In conclusion, our study demonstrated that metabolic perturbation of chromatin status in oncogene-activated cancers could be an optional intervention to sensitize DNA damage response signaling.